Obesity, inflammation, and depression in adolescents - McLachlan, Caleb; Shelton, Richard; Li, Li (Frontiers in Psychiatry, 2023)
Background: The prevalence of depression and obesity amongst adolescents has markedly increased over the last few decades. A bidirectional relationship has been proposed between depression and obesity in adolescence, but it remains poorly understood. Inflammation is a phenomenon that has been implicated in both disorders. Thus, a cross-sectional study was designed to investigate inflammation as a factor in the association between obesity and depression. The goal of this study is to better understand the interplay between these two disorders.Methods: The study sample consisted of female and male, black and white adolescents aged 15-18 years. Participants were diagnosed with major depressive disorder (MDD) according to the Diagnostic and Statistical Manual of Mental Disorders-5. Depression severity was determined using the Quick Inventory of Depressive Symptomatology (QIDS). Participants completed the Childhood Trust Events Survey (CTES) and received an Early Life Stress (ELS) score based on the survey results. Those with a score of ≥4 were placed in the ELS group and those with a score ≤3 were placed in the non-ELS group. Anthropometric measures and a Dual Energy X-ray Absorptiometry (DEXA) scan were performed for body composition. Blood samples were collected to measure inflammatory factors. Results: Adolescents with MDD (n=47) had significantly elevated body mass index (BMI) percentiles compared to the controls (n=47), (77.11±3.58 vs. 59.63±4.40), and increased adiposity measures, including total fat (p=0.016), trunk fat (p=0.016), and trunk/total fat ratio (p=0.021).Levels of C-reactive protein, tumor necrosis factor-alpha, interleukin-6, leptin, and adiponectin varied significantly between the MDD and control groups, however, significance was not retained when BMI percentile and ELS score were controlled. There was a significant and positive relationship between QIDS and multiple measures of adiposity such as BMI percentile, visceral abdominal tissue, and trunk/total ratio. Depression severity was best predicted by ELS score, visceral adipose tissue, and adiponectin level.Conclusions: Adolescents with MDD had increased levels of inflammatory factors and many measures of adiposity. Thus, the treatment of adolescent depression should include a focus on managing body composition and reducing chronic inflammation to potentially improve treatment outcomes.